Como sustentar os/as pregadores/as a fim de que não abandonem o ministério de Deus na Igreja Evangélica Luterana de Angola (IELA)? - Wima, Filipe Cambongue (2014)
This paper intends to analyze the ways in which preachers have been sustained in the context of the Evangelical Lutheran Church of Angola (IELA) from its inception to the current days. The economic difficulties, the social conditions of the preachers and the lack of teaching the Word of God related to the contributions for the cause of the Christian faith, to the members of the congregations have presented great limitations to the pastoral and missionary work. Consequently, this affects the development of the IELA in all dimensions: economic, geographic, numerically and poimenically. The IELA seeks paths which point in the direction of autonomy in a broad sense. Therefore, the research aims at helping in the comprehension of the context in which the church finds itself, thus permitting a clearer perception of the limits and possibilities of the work of the Lutheran preachers in Angola.